The VEGETABLE INTAKE, PHYSICAL ACTIVITIES AND OBESITY STATUS OF SEKA TERUNI EKA MANGGALA DANENDRA MEMBERS - Kadek Paramahita Dwitami; I Putu Suiraoka; I Wayan Ambartana (POLTEKKES KEMENKES JAYAPURA, 2022)
The prevalence of obesity in Indonesia for adults >18 years old increased from 10,5% in 2013 to 21.8% in 2018. This study aimed to determine the correlation between vegetable intake and physical activities with the obesity of Seka Teruna Teruni (STT) Eka Manggala Danendra Banjar Tengah. The type of research used was analytic observational with a cross-sectional design. The statistical test used the Spearman Rank correlation test. The research sample amounted to 64 people, with the sampling method being a non-probability random sample. The results showed that most of the respondents had a low level of vegetable intake (96.9%), the level of physical activities of the respondents was mostly moderate (54.7%), and there were 12 (18.8%) respondents with obesity. The physical activity conditioning with obesity status was significantly related with the p-value = 0.004 < (0.05) and the value of coefficient correlation = -0.356, which means that there was a significant and not unidirectional relationship between the level of physical activities and obesity status in members of STT Eka Manggala Danendra in 2022. The story of physical activities is a variable that affects a person's obesity status. Therefore, education about increasing physical activity and vegetable intake is needed to maintain the ideal body weight. Keywords: Obesity, Physical activities, Vegetable intake